Educação ambiental como instrumento de política pública contra o descarte desordenado de resíduo tecnológico - OLIVEIRA, Moises Santiago de (Universidade de São Paulo, 2023)
The article aims to discuss essential topics for understanding the theme of environmental education. In this context, certain crucial issues for the development of this work will be presented, namely: capitalism, planned obsolescence, hyperconsumption, environmental policy and legislation, reverse logistics, selective collection and the governance/accountability process. The study was carried out from the theoretical survey of articles in national databases, books and official documents. Throughout the article, the following topics will be addressed: capitalism and the use of programmed obsolescence as a means for the constitution and maintenance of hyperconsumer societies.